Genealogy and the History of Catholicism in Modern Shanghai - 李强 (Journal of Research for Christianity in China (JRCC), 2025)
A large amount of Chinese had converted to Catholicism, since the late Ming dynasty. As a result, many Catholicism lineages had formed. They still retained traditional social custom in editing their pedigrees like other non-Catholicism lineages did. It is universally known that Pedigree Documents are valuable in studying Chinese historical figures. Remarkably, there was a flourish development of Catholicism in K’iang-nan district including Shanghai, during the late Qing and early Republic of China period. By studying several pedigree documents colleted by Shanghai Library which have relevant relation with Catholicism, will be helpful to study the history of those Catholicism lineages and some famous figures of modern Shanghai Catholicism church, especially in expanding our knowledge about several Chinese native clergies (e.g., Petrus Hoang, Laurentius Li, Firmino Chen, etc.).